THE EFFECT OF PROACTIVE PERSONALITY ON WORK PRODUCTIVITY - Susan Novrini; Syaifuddin Syaifuddin; Fajar Rezeki Ananda Lubis (Journal of Information Systems Management and Digital Business, 2026)
The productivity or decline in the quality of a company is often caused by various internal and external sectors of the institution itself. The decline in the quality of a company is inseparable from the role of leaders and employees who work in it. This is because the role of employees is very important in a company. This study examines the effect of proactive personality on work productivity at PT Perkebunan Nusantara III. The sample size was 292 respondents, selected using purposive sampling. Data analysis used Structural Equation Modeling - Partial Least Square (SEM PLS). The results showed that proactive personality directly affects work productivity with a T statistic of 4.618, greater than 1.96, with a p value of 0.000, less than 0.05. The magnitude of the influence of proactive personality on work productivity is 0.234, or 23.4%. Therefore, several practical implications are needed for company management, including the need to foster employee involvement and encourage employee initiative and proactivity.